Strategy Ecotourism in Perlis Malaysia To Become One Of Malaysia’s Top Destination - Deliana, Dian (Institute of Education and Social Research, 2024)
Perlis has extraordinary natural wealth with green rice fields, stunning mountains, and rich biodiversity. This indicates great potential for ecotourism development in this area. The aim of this research is to explore ecotourism strategies in Perlis Malaysia to become one of the main destinations in Malaysia for sustainable ecotourism. This research adopts a qualitative method that places the researcher as the main instrument, carries out triangulation techniques for data collection, and applies inductive analysis. The research results show that cross-institutional collaboration is key to optimizing the tourism potential of the Perlis ecotourism area, creating positive effects for the local community and the tourism industry as a whole. The availability of amenities and public facilities in the Perlis ecotourism area is still not optimal, and promotion plays a crucial role in introducing, convincing, and maintaining interest in certain tourist products or destinations. In this case, the use of effective promotional media is the key to increasing the popularity and public awareness of Perlis ecotourism. Promotional strategies must take into account variations in audience interests and utilize various marketing tools, such as advertising, face-to-face sales, and publicity, to achieve optimal marketing goals.